Contemporary security management - Fay, John (Boston : Butterworth-Heinemann, 2002)
The book draws heavily from current, experience-proven business practices applicable to security operations.
Includes bibliographical references and index.
uaj 20/02/2015
Loans
Keywords: Private security services; Industries - security measures; Personnel management; Security management